p38γ and p38δ Are Involved in T Lymphocyte Development - Risco, Ana; Martin-Serrano, Miguel A.; Barber, Domingo F.; Cuenda, Ana (Frontiers in immunology, 2018)
p38 mitogen-activated protein kinase (MAPK) signal transduction pathways are essential regulators of the immune response. Particularly, p38γ and p38δ regulate many immune cell functions such as cytokine production, migration, or T cell activation; however, their involvement in immune cell development is largely unknown. Here, we analysed the role of p38 MAPK isoforms p38γ and p38δ in T cell differentiation in the thymus and in lymph nodes, using mice deficient in p38γ, p38δ, or in both. We found that the T cell differentiation program in the thymus was affected at different stages in p38γ-, p38δ-, and p38γ/δ-deficient mice, and also peripheral T cell homaeostasis was compromised. Particularly, p38δ deletion affects different stages of early CD4 CD8 double-negative thymocyte development, whereas lack of p38γ favours thymocyte positive selection from CD4 CD8 double-positive to CD4 or CD8 single-positive cells. Our results identify unreported functions for p38γ and p38δ in T cells.